PENGARUH TAMPILAN TOKO ( STORE ATMOSPHERE ) TERHADAP KEPUASAN KONSUMEN PADA UKM KULINER DI KELURAHAN DEPOK JAYA, KECAMATAN PANCORAN MAS, KOTA DEPOK. - faisal H Batubara; chairul hadi (Prosiding Seminar Nasional Manajemen Industri dan Rantai Pasok, 2021)
The culinary business is compared to other businesses in the city of Depok during the pandemic, its development is ranked first, this is what makes the author interested in conducting research on "The Effect of Store Atmosphere on Consumer Satisfaction in Culinary SMEs in Depok Jaya Village, Pancoran Mas District. , Depok City” (Case Study of Mang Kumis and Mang Dadang Pancong Cakes). This study aims to determine how much influence the store display has on consumer satisfaction. This study examines the variables, namely the independent variable (store appearance) can affect the dependent variable (consumer satisfaction). The sample in this study was 41 respondents and the data in this study used a survey method through questionnaires filled out by consumers. Data obtained by using simple linear regression analysis, hypothesis testing through r test and t test and the Coefficient of Determination (R.Square) test. The results of the correlation coefficient test (r test) yielded 90.7%, this shows that the relationship between the dependent variable and the independent variable is very strong and positively correlated. The result of the partial test (t test) is the ttable value at a significant level of 5%, which is 2.022691. Due to the value of tcount = 13,434 > ttable = 2,023, then H0 is rejected. This shows that the store display significantly affects consumer satisfaction. The results of the Coefficient of Determination (R Square) test in this study are the influence of the independent variable on the dependent variable of 0.822, meaning that consumer satisfaction is influenced by store appearance by 82.2% and the remaining 17.8% is influenced by other factors (other variables) outside the study.Keywords: influence, store appearance, customer satisfaction